The Invisibility of Street Know-How in the Training of Circus Artists in Brazil - Barreto, Lua; Coelho Bortoleto, Marco Antonio (Revista Brasileira de Estudos da Presença, 2025)
The relationship between circus schools in Brazil and the training of artists who perform in street and open spaces was the goal of this study. Five schools were analyzed through a review of pedagogical programs, interviews with teachers and coordinators, and a questionnaire completed by former students. Despite the recognition of the street as a relevant space for performing and its high demand, there is no systematic approach aimed at developing specific skills for street circus performance, suggesting the institutionalized absence of this know-how in the training provided by the schools studied.